Spontaneous Pneumothorax in a Young Child With Pulmonary Tuberculosis. Issue 12 (December 2018) - Hulme, Kathryn M.; Isaacs, David; Marais, Ben J.; Robinson, Paul D.
Abstract : We report a 2-year-old, previously healthy boy, who presented with chronic pneumonia. He was diagnosed with culture-confirmed pulmonary tuberculosis. Complications included spontaneous pneumothorax presumed to be secondary to cavity formation and complete subsegmental airway obstruction that did not resolve with prolonged oral corticosteroid treatment.